Health providers as bricoleurs: an examination of the adaption of health ecosystems to superdiversity in Europe - Phillimore, J.; Bradby, H.; Doos, L.; Padilla, B.; Samerski, S. (Journal of European Social Policy, 2019)
This article examines the ways in which healthcare providers from a mixed economy of welfare operating in superdiverse neighbourhoods connect and innovate across the healthcare ecosystem to meet diverse and complex needs. Moving beyond a health systems approach which siloes different types of provision, we use the concept of bricolage to make visible the work undertaken by providers across the ecosystem. While we show that public, private and civil society provision all adapt to meet complex and diverse needs to some degree, we highlight the importance of inter-connectedness between providers and note the role of civil society in addressing gaps and cracks in provision. The importance of adopting a whole ecosystem approach and focusing on the actions and interactions which enable the ecosystem to function in complex demographic environments is highlighted before we stress the dangers of over-reliance on civil society.